Natural weathering performance of three fast-growing Eucalypt woods - Gonzalez de Cademartori, Pedro Henrique; Missio, André Luiz; Dufau Mattos, Bruno; Gatto, Darci Alberto (Maderas. Ciencia y Tecnología, 2025)
We investigated the effect of outdoor exposure on the wood surface from three fast-growing Brazilian eucalypts through color, wetting and thermal analyzes. Gympie messmate (Eucalyptus cloeziana), rose gum (Eucalyptus grandis) and blue gum (Eucalyptus saligna) woods were exposed outdoors in a subtropical region for 360 days. We performed three collections every 120 days. We investigated color changes of untreated and weathered woods through a spectrophotometer (CIEL*a*b* system) and changes in macro compounds of wood through thermogravimetric analysis. In addition, the apparent contact angle and work of adhesion were evaluated using a goniometer. Outdoor exposure for 120 days provided significant increment in grayish of wood surface. Thermogravimetric curves of wood changed after the weathering, especially in the regions related to hemicelluloses and lignin thermal degradation. Outdoor exposure for 360 days converted hydrophilic wood surface into a very hydrophilic one, wherein occurrence of microcracks contributed to fully spreading of water droplets.